2006
DOI: 10.3368/jhr.xli.2.380
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Literacy on Immigrant Earnings

Abstract: a b s t r a c tWe examine the impact of literacy on immigrant earnings and the sources of lower returns to education and experience among immigrants. We find that the native-born literacy distribution dominates that for immigrants. However, the two groups obtain similar returns to literacy skills, contrary to discrimination-based explanations for immigrant-native-born earnings differentials. Among the university-educated, literacy differences account for about two-thirds of the earnings gap. However, low retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
112
3
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(122 citation statements)
references
References 24 publications
5
112
3
2
Order By: Relevance
“…In previous research using the 1994 IALS data we found that there is a surprisingly weak relationship between literacy skills and age, after controlling for other influences (Green and 1 Riddell, 2003;Ferrer, Green and Riddell, 2006). In this paper we investigate the relationship between literacy skills and age more thoroughly using the much larger sample provided by the 2003 IALSS data.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research using the 1994 IALS data we found that there is a surprisingly weak relationship between literacy skills and age, after controlling for other influences (Green and 1 Riddell, 2003;Ferrer, Green and Riddell, 2006). In this paper we investigate the relationship between literacy skills and age more thoroughly using the much larger sample provided by the 2003 IALSS data.…”
Section: Introductionmentioning
confidence: 99%
“…Low levels of literacy are a factor negatively a ecting the social and economic integration of immigrants (Ferrer et al 2006, Kahn 2004. Non-native speaking immigrants face an economic decision to acquire a host-country language (Selten andPool 1991, Chiswick andMiller 1995).…”
Section: Introductionmentioning
confidence: 99%
“…While not directly relevant to health professionals, a similar problem is noted by Ferrer, Green, and Riddell (2006) among Canadian immigrants in general. There appears sometimes to be a gap between literacy/language skills as measured by these tests and individuals' self perception.…”
Section: Test Of English As a Foreign Language (Toefl) And The Test Omentioning
confidence: 96%